Al-HallÃ¢j Sebagai Korban Politik atau Transgresor Teologi - Hodri, Hodri (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2011)
The article attempts to reveal al-Hallâj?s history of thought that caused his death as he was considered an apostate who violated religious boundaries. On several occasions, moreover, al-Hallâj was made as a sort of warning for those ?cheat? with religious issues will be firmly punished by death penalty. It has been rarely clarified that Al-Hallâj was, in fact, a political victim by divulging religious issues as the main reason. As a concept, Hulûl, which becomes the main doctrine of al-Hallâj, has been often misunderstood and seen as a conduct that leads to apostasy. The reason is that its founder was executed by the death penalty as he was accused as being an apostate. On the other side, such view is not quite surprising, since the level of understanding held by the majority of Muslims has, in fact, been within khitâbî level. It has caused them hard to properly and correctly understand such philosophical discourses as hulûl, ittihâd, or wahda al-wujûd. This condition has been worsened by the fact that literatures on al-Hallâj and hulûl, especially in Indonesian language, are rare. After centuries, the idea of hulûl has been frequently misunderstood. However, careful study will show that hulûl, like other Sufi?s doctrines, is Sufism experience expression of al-Hallâj when he felt the presence of God, i.e. the encounter of human?s lâhût with God?s nâsût. Therefore, the execution of al-Hallâj has been based on more political interest than theological reason.